지속가능발전목표 관점에서 토픽모델링을 활용한 지속가능한 도시 연구 동향 분석 - 김경아; Gyeonga Kim; 김선희; Sunhee Kim (환경정책, 2021)
본 연구의 목적은 국내 지속가능한 도시에 관한 연구 동향을 분석하고, 향후 연구의 발전 방향을 제시하는 것이다. 이를 위하여 연구 방법은 토픽모델링 분석 방법을 사용하였으며, 1993년부터 2020년 11월까지의 한국학술지인용색인(KCI)에 게재된 지속가능한 발전 연구대상으로 지속가능한 도시의 연구 동향을 분석하였다. 분석 결과, 지속가능한 도시에 관한 연구는 5개의 주제로 분류되었으며, 5개의 주제는 하나의 네트워크로 연결되어 있었다. 이 중 도시의 자원 및 에너지 관련 연구가 시기적으로 가장 큰 비중을 차지하고 있었다. 또한, 도시성장 관리와 거버넌스 연구가 활발하게 진행되고 있는 경향을 보였다. 그리고 시민 키워드는 네 개의 토픽을 연결하는 것으로 나타나 지속가능한 도시에서의 시민참여의 중요성을 확인할 수 있었다. 반면 문화유산, 대기, 폐기물, 녹지 관련 연구는 미비한 것으로 나타났다. 이러한 결과를 바탕으로 지속가능한 도시연구에 대한 현황을 파악하는 정보를 제공하고, 향후 지속가능한 도시 연구의 연구 방향을 제안하였다. The purpose of this study is to analyze research trends surrounding sustainable cities in Korea and to provide a direction for future research. For this purpose, the research method used was Topic Modeling, and research trends in sustainable cities were analyzed by surveying subjects of sustainable development research published in the Korean Journal Citation Index (KCI) between 1993 to November 2020. As a result of this analysis, research on sustainable cities was classified into five topics, and these five topics were linked to a single network. Of those, research related to urban resources and energy accounted for the majority of papers published. Furthermore, research related to urban growth management and governance studies has been active for many years. Also, we found that there was an overlap in citizen keywords in four topics, thus confirming the importance of citizen participation in a sustainable city. On the other hand, studies related to cultural heritage, atmosphere, waste, and green space were sparse. Based on these results, we have provided information about the current status of sustainable city research and propose research directions for future sustainable city studies.